Defining Experiential Education for Applications in Higher Education: A Call to Action - Heinrich, Bill; Green, Patrick M. (Experiential Learning and Teaching in Higher Education, 2025)
As the context of experiential learning has evolved over the last several decades, we argue this is a moment of inflection. This essay follows a human-centered design process to update the definition of experiential education (EE) for the Society for Experiential Education (SEE). The authors stewarded a 20-month process to identify needs, define the challenge, develop solutions, and create prototypes. Data collection, reflection, and transformation occurred through dozens of conversations with hundreds of stakeholders from the broader EE community and SEE members, stakeholders. The prototype definitions are here! In the context of an experientially focused and practical project, the authors share and reflect upon three emergent prototype definitions. The prototypes reflect the needs of both educators and community partners throughout the experiential learning ecosystem. The reflections help us connect this project back to the broader landscape of evidence-driven practice in North American higher education.